2021
DOI: 10.1111/vco.12778
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin preferentially inhibits the growth of high ZEB‐expressing canine cancer cells

Abstract: The epithelial‐to‐mesenchymal transition (EMT) is fundamental in cancer progression and contributes to the acquisition of malignant properties. The statin class of cholesterol‐lowering drugs exhibits pleiotropic anticancer effects in vitro and in vivo, and many epidemiologic studies have reported a correlation between statin use and reduced cancer mortality. We have shown previously that sensitivity to the anti‐proliferative effect of statins varies among human cancer cells and statins are more effective again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We have previously reported that even atorvastatin, which has relatively weak anticancer properties among lipophilic statins, exerts marked anticancer effects against human and canine melanoma with a mesenchymal phenotype. 10,12 Our results showed that pitavastatin was the most effective in all cell lines tested in this study, which provides novel insights into selecting the optimal statin for treating canine melanoma.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We have previously reported that even atorvastatin, which has relatively weak anticancer properties among lipophilic statins, exerts marked anticancer effects against human and canine melanoma with a mesenchymal phenotype. 10,12 Our results showed that pitavastatin was the most effective in all cell lines tested in this study, which provides novel insights into selecting the optimal statin for treating canine melanoma.…”
Section: Discussionmentioning
confidence: 60%
“…Three canine oral melanoma cell lines, previously established by Osaki et al, 20 with mesenchymal phenotype, 12…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies showed that atorvastatin is effective against all melanoma cells in both human [ 14 ] and spontaneously occurring canine melanoma cell lines [ 15 , 16 ]. Furthermore, plasma levels of atorvastatin, comparable to those used for the treatment of hypercholesterolemia, have been reported to inhibit the metastasis of human melanoma cells overexpressing RhoC in a xenograft model [ 17 ].…”
Section: Introductionmentioning
confidence: 99%